Konstruksi Sosial Selebriti di Dunia Politik: Implikasi Pendidikan dan Pengaruh Media - Lisna Anggi Putri; Muhammad Dawud Abdul Halim; Mochammad Shafwan Daffa; Ariya Aurel Megantara; Syavira Maharani Nurjaman; Erika Rahmadani; Supriyono Supriyono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The social construction of celebrities in the world of politics has become a phenomenon that attracts attention, especially in relation to educational empowerment and media influence. Celebrity-driven voter campaigns often elicit positive responses from younger audiences, who may previously be less interested in political issues. Thus, collaboration between education and media not only increases political awareness but also encourages active community involvement. This research uses qualitative methods with a literature study approach, analyzing previous research to understand the role of celebrities in influencing involvement in the realm of political society. The research results show that celebrities play an important role in increasing people's political awareness. Education contributes to the political understanding of celebrities, who often use their platforms to spread information about political issues. Media, especially social media, amplifies these messages and allows direct interaction with fans, encouraging political participation, especially among the younger generation. Voter campaigns promoted by celebrities often attract the attention of audiences previously less interested in politics. This research confirms that celebrities are not only entertainment figures, but also agents of social change who have the potential to influence political dynamics through education and the media.